Distribution channels of analyst research: new evidence - Amiram, Dan; Bozanic, Zahn; Bradshaw, Mark; Rozenbaum, Oded (Review of Accounting Studies, 2025)
The channels through which analyst research data are distributed are complex. The I/B/E/S database is the dominant source for analyst earnings estimates for academics, but there are numerous other channels, some of which are cost prohibitive for many investors. We describe the distribution of analyst research and examine whether a high-cost alternative distribution channel, TR Research, is characterized by higher quality estimates than those available from I/B/E/S. We examine analyst forecast accuracy, bias, and informativeness and find that TR Research estimates are more accurate and less biased than estimates exclusively distributed via I/B/E/S. We further find that TR Research estimates are associated with greater market reaction and lower information asymmetry, consistent with the higher quality of these estimates. Our study highlights differences in brokerage and analyst incentives regarding research distribution and documents a specific setting where a subset of investors pays for access to superior analyst research.